Analisis Kinerja Keuangan Antar Bank Umum Milik Negara Yang Terdaftar Di BEI Tahun 2019-2021 - Febiyanto; Deny Edy Widodo; Qori’Ah Sholihah (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aims to determine differences in financial performance between state-ownedcommercial banks using the CAMEL ratio to determine whether the bank's performance is inthe healthy predicate or not. In this study identified Bank Rakyat Indonesia (BRI), BankMandiri, Bank Negara Indonesia (BNI), State Savings Bank (BTN), in 2019-2021. Thisresearch method is calculated using the ratio of Capital, Assets, Management, Earnings,Liquidity (CAMEL). The results of this study use the CAR, NPL/NPF, NPM, and LDR ratiosof the five state-owned commercial banks in the 2019-2021 period with different predicates.Bank Rakyat Indonesia and Bank Tabungan Negara tend to get healthy predicates, whileBank Nasional Indonesia and Bank Syariah Indonesia have various predicates. However,Bank Mandiri tends to have an unhealthy predicate in 2019-2021 based on the NPL ratio.For the ROA ratio of the five state-owned commercial banks, it tends to get a healthypredicate, only in 2019 and 2021 the State Savings Bank has an unhealthy ROA ratio. As forthe BOPO ratio, the five state-owned commercial banks tend to be unhealthy in the 2019-2021 period. Therefore, it is necessary to make efforts to improve the financial performanceof these banks in order to make a greater contribution to the national economy. For the LDRratio of the five state-owned commercial banks for the 2019-2021 period it tends to behealthy, the State Savings Bank for the 2019-2021 LDR ratio tends to be unhealthy.